Tactile Sign Language of People with Deafblindness - Jablan, Branka; Alimović, Sonja; Vučinić, Vesna (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Deaf-blindness is a dual sensory impairment and adversely affects different areas of a person’s functioning. Thus, there is a need for an individualized approach to education and rehabilitation, as well as specific services that facilitate learning, participation, and social inclusion. The study of this phenomenon is accompanied by challenges arising from the lack of consensus on the definition of deaf-blindness, the heterogeneity of the population, and the lack of reliable tests and tools for assessment. Furthermore, the use of traditional procedures that are often based only on the determination of sensory functioning, as well as insufficiently efficient and untested working methods, hinder the development of communication with a person who is deafblind. Objectives. The aim of this paper was to analyze the specific communication methods of people with deaf-blindness and, in particular, to analyze and describe tactile sign language. Methodes. The service of the Consortium of Libraries of Serbia for unified acquisition – KOBSON and Google Scholar Advanced Search were used for the search and analysis of relevant studies. Searches were performed using the following services/ aggregators: Ebscohost, ScienceDirect, and WileyInterScience. Results. Communication of people with deaf-blindness can occur through a variety of modalities: speech, sign language, finger alphabet/alphabet, manual alphabet/manual alphabet, Lorm’s alphabet, palm writing, Tadoma method, written language, Braille, enlarged print, tactile sign language. In recent studies, authors emphasize the need to develop a unique tactile sign language as a natural language of persons who are deafblind from birth.